PENGEMBANGAN PERANGKAT MODEL PEMBELAJARAN KUANTUM BERBASIS MASALAH DENGAN PENDEKATAN SAINTIFIK - Mei Indra Jayanti; A. Wahab Jufri; Agus Ramdani (Jurnal Penelitian Pendidikan IPA, 2015)
In the Law of the Republic of Indonesia Number 20 of  2003 on the national education system of article 1, paragraph 1 that education will be successful in learning activities where students are able to achieve the expected competencies of science and give a positive value to themselves. Critical thinking ability and reasoning ability is part of the high school biology course goals that can be developed through a student-centered learning, such as quantum learning, problem-based learning, and scientific approach. This study aimed to develop the quantum problem-based learning model packages and the quantum without problem-based learning (PKBM and PKTBM) with 4 and 6 stage of scientific  approach  toward critical thinking ability and  reasoning ability in tenth grades. Process of development teaching and learning packages refers to the model Dick & Carey. Teaching and learning packages developed to biology course for the tenth grade of senior high school in ecological material. Data were  collected by using instruments feasibility characteristics of teaching and learning packages. Data were analyzed using descriptive statistics. The results showed that the syllabus and the learning lesson plan (LLP)  got a worthy category; worksheets, tests of critical thinking ability and tests of reasoning ability got a very worthy category to used in tenth grades of senior high school.Keywords: PKBM, PKTBM, scientific approach, critical thinking ability, reasoning ability